PENDIDIKAN BUDI PEKERTI MENJADI MATA PELAJARAN DI SEKOLAH - Setyowati, Erna (Universitas Negeri Semarang, 2009)
The globalisation era influences the shift in moral values and studentsbehavior. This is reinforced with the the fast growing informational technology whichdevelops in a matter of seconds.As a result, negative foreign culture is easily absorbedwithout a sufficient filter. Today what happens at one part of the world can be directlymonitored from other parts of the world. In the globalization, students think critically.The border of moral values is very slight. The example from biraucrats is regardedpoor. There are many vulgar moral values exposed to young generations. Theexposure has a negative risk for the students. This condition becomes a quite fatalweak point for educators to implant good conduct at schools and homes. The goodconducts education at schools is stepping backward. Emphirically teachers hardlyever teach good conducts at schools. Students behaved impolitely to teachers anddespised their peers. This is because good conducts as a subject which standsindependently from other subjects does not exist. The subject was integrated into twosubjects: civics and religion education. However, this is regarded as a failure. Thesubject still fails even when it was integrated with mathematics, science, socialscience, arts, Indonesian, and physical education. Good conducts should be includedin the curriculum as an independent subject. The assessment should emphasize theability to apply good conducts in every day life.Kata kunci : pendidikan budi pekerti, sekolah, dan etika